A Rarely Seen Infection in Emergency Departments: Tularemia, Which Can Cause Outbreak - Gulacti, Umut; Lok, Ugur; Ustun, Cemal; Atescelik, Metin; Guger, Mehtap; Yanilmaz, Muhammet (Emergency Medicine Physicians Assoc Turkey, 2014)
Tularemia is a zoonotic bacterial infectious disease; its causative agent is Francisella tularensis. Tularemia can lead to outbreaks. The infection may cause severe complications from cutaneous ulceration and regional lymphadenopathies on the transmitting area of the body to fever, pneumonia, or sepsis. Due to the difficulty of diagnosis, tularemia should be considered in the differential diagnosis; otherwise, it can be missed easily. Tularemia should be kept in mind in the differential diagnosis of patients with sore throat, lymphadenopathy, and neck mass. If not diagnosed timely and treated adequately, it can lead to mortality.
Keywords: Tularemia; neck mass; sore throat; outbreaks